Subduing Cultural Stereotype & Ethnocentrism in Business Organizations: A Soft Skills Stance - Mitashree Tripathy (Institut Teknologi Sepuluh Nopember, 2019)
Business organizations are highly dependent on culture and communicationthat define the essence of their existence. Researches indicate that while someorganizations have successfully placed themselves in the global marketplaces, there are still others who have deteriorated because of weakcommunication or insufficient assimilation with other organizations ofdifferent cultures. Recent studies argued that the accomplishment of theglobal business depends on successful cross cultural communication. Thispaper studies the role of cross cultural communication and the barriers thatobstruct cross cultural effectiveness in business. The paper especially focuseson the cultural stereotype and ethnocentrism as the most powerful barriersin cross cultural communication and proposes solutions towards therelevance of soft skills in overcoming the barriers and ensuring success inbusiness in unprecedented ways and their development in cross culturalmanagement.